Beating Around the Bush: Reflections on the Theme - Terry Evans (Journal of Research in Rural Education, 2003)
The editors (Geoff Danaher, Beverley Moriarty, and Patrick Alan Danaher) of this special issue have chosen to draw attention to the rural/urban dualism and to provide a critique of its consequences in terms of our conceptualization of societies in general and of education in particular. They argue that this dualism is, in effect, a modernist/essentialist distinction. It is also seen that such binaries are flawed in practice: it is easy to say what is urban and what is rural, but a lot of geography and humanity exists in between and beyond. (Just where does the outback start in Australia?). This flawed binary between urban and rural also positions the rural as the negative (poor, unsophisticated, undeveloped) corollary of the urban (rich, sophisticated, developed). For me, there are echoes here of the equally problematic binary of developed/developing nations (Evans, 2003).